Career intentions of final year medical students in Uganda after graduating: the burden of brain drain - Kizito, Samuel; Mukunya, David; Nakitende, Joyce; Nambasa, Stella; Nampogo, Adrian; Kalyesubula, Robert; Katamba, Achilles; Sewankambo, Nelson (BMC Medical Education, 2015)
Background: Uganda has severe shortage of human resources for health despite the heavy disease burden. The country has one of the highest fertility, and population growth rates in the world and is in dire need of trained health workers. The current doctor: patient ratio of 1:15000 is inadequate and this is further constrained by trained health workers leaving the country while others abandon the health sector. The aim of the study was to determine the career intentions of the final year medical students to leave the county and health field after graduating and the associated factors. Methods: We conducted a cross-sectional study among 251 final year medical students from Makerere, Mbarara, Gulu and Kampala International Universities. We enrolled all the eligible final year medical students. The study was conducted using face-to-face questionnaires in each university. We determined the demographics, reasons for leaving the country and health sector and the intended destinations of medical students who planned to leave the country. Data was entered in Epidata then exported and analyzed in stata 12. Results: Of the 251 students enrolled in the study, 28(11.2 %) wanted to leave the health sector, with Mbarara University of Science and Technology (MUST) having the highest percentage, 16.7 % and Kampala International University (KIU) the least, 7.7 %. Of the 28 who intended to leave the health sector, 82.1 % wanted to join the business sector, 10.7 % agriculture, and 7.1 % politics. Reasons given for the intent to leave were; lack of equipment and supplies in hospitals, over whelming patient numbers, very risky working environment, low payment to doctors, and political reasons. Overall, 112 (44.6 %) of the participants wanted to leave the country with 30.3 % intending to migrate to United States of America (USA), 11.9 % to United Kingdom (UK), 11.0 % to South Africa among others. Some of the reasons given were; doctors are paid a high salary abroad, safe working environment, and desire to continue academics. Age was associated with intention to leave the country (OR = 1.64; 95 % CI: 1.00 – 4.82). Conclusions: In a country in dire need of health workers, the study showed high proportion of trainee health workers planning to abandon their professions or emigrate from Uganda after training
Keywords: Brain-drain; Doctors; Uganda